Animals and Social Work: A Moral Introduction - Ryan, T. author. aut Link
X, 209 p.
Keywords: Social Work and Animals represents a pioneering contribution to the literature of social work ethics and moral philosophy. It advances cogent and detailed arguments for the inclusion of animals within social work's moral framework, arguments that have profound theoretical and practical implications for the discipline and its practitioners.